Diatomic pair catalyst for nitrile compound hydrogenation and preparation and application thereof
By uniformly supporting rhodium-cobalt diatoms on the nanodiamond/graphene composite material to form a catalyst with atomic dispersion, the problems of low metal utilization and high reaction conditions in the hydrogenation reaction of nitrile compounds are solved, and the problem of low metal utilization and high reaction conditions of existing catalysts is achieved. Highly efficient and selective secondary amine synthesis.
Patent Information
- Application Number
- CN202411549668.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
In the hydrogenation reaction of nitrile compounds, existing catalysts have problems such as low metal utilization, environmental pollution and high temperature and high pressure required for reaction conditions, and single-atom catalysts have adsorption limitations in catalyzing the hydrogenation reaction of larger organic molecules.
Nanodiamond/graphene composite materials are used as support and rhodium-cobalt diatoms are used as active materials. Rhodium and cobalt atoms are uniformly supported by deposition and precipitation and electrostatic adsorption to form a catalyst for atomically dispersed rhodium-cobalt nanodiamond/graphene composite materials.
Under mild conditions, the catalytic performance and selectivity of the hydrogenation reaction of nitrile compounds are significantly improved, and the high conversion and selective synthesis of secondary amines are achieved, the catalyst cost and energy consumption are reduced, and the catalyst is environmentally friendly and efficient.
Smart Images

Figure BDA0005114728750000051 
Figure HDA0005114728760000011 
Figure HDA0005114728760000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic chemical raw material synthesis, and specifically relates to a diatomic pair catalyst for hydrogenation of nitrile compounds and a preparation and application thereof. Background Art
[0002] In the chemical industry, secondary amine compounds, as important organic synthesis intermediates, play a key role in the fields of pesticides, medicines, etc. The hydrogenation of nitrile compounds is an effective method for preparing high value-added secondary amines. Although a variety of catalysts have been developed for catalyzing the hydrogenation of nitrile compounds to prepare secondary amines, there are still some problems, such as low metal utilization (especially precious metals) and environmental pollution. At the same time, traditional reaction conditions usually require high temperature and high pressure, and the products are complex and the selectivity is difficult to control. Therefore, it is very important to develop catalysts with high catalytic performance under mild reaction conditions.
[0003] In recent years, single-atom catalysts have shown excellent catalytic performance in a variety of reactions, especially for supported precious metal catalysts, where metal atoms can be dispersed at the atomic level on the surface of the carrier, achieving 100% metal atom utilization, thereby saving catalyst costs. In the nitrile hydrogenation reaction, some metal single-atom catalysts (such as palladium single-atom catalysts supported on silicon oxide) also show good catalytic performance. However, single-atom catalysts have limitations in the catalytic hydrogenation reaction of nitrile compounds. Their single active site fixed adsorption mode and relatively weak adsorption capacity make it difficult to catalyze the hydrogenation of larger organic molecules.
[0004] A diatomic catalyst is formed by two different metals in close proximity to each other, which can effectively solve the adsorption limitation problem of single-atom catalysts. A diatomic catalyst can adsorb multiple substrate molecules at the same time, improving the adsorption limitation of single-atom catalysts and thus improving the catalytic performance. At the same time, the interaction between the two metals can not only improve the stability of the catalyst, but also regulate the electronic structure of the metal surface and reduce the apparent activation energy of the reaction. However, the diatomic catalysts currently used in the hydrogenation reaction of nitrile compounds still need further research and development. Summary of the invention
[0005] The purpose of the present invention is to provide a diatomic pair catalyst for hydrogenation of nitrile compounds and its preparation and application. When the prepared atomic-level dispersed rhodium-cobalt nanodiamond / graphene composite material catalyst is used for hydrogenation of nitrile compounds to prepare secondary amines, it can efficiently catalyze the hydrogenation of nitrile compounds to secondary amines under mild conditions.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A diatomic pair catalyst for hydrogenation of nitrile compounds uses a nanodiamond / graphene composite material as a carrier and rhodium-cobalt diatoms as active materials. Rhodium and cobalt are uniformly loaded on the surface of the nanodiamond / graphene composite material carrier in the form of diatomic pairs and form bonds with carbon atoms on graphene defects.
[0008] The nano-diamond / graphene composite material is a core-shell structure formed by taking nano-diamond as a core and graphene rich in defects as a shell.
[0009] In the catalyst, the content of rhodium is 0.15wt%-1.0wt% of the carrier mass, and the content of cobalt is 0.25wt%-0.75wt% of the carrier mass.
[0010] In the process of hydrogenation of nitrile compounds to generate secondary amine compounds, when the reaction time is 6h to 8h, the product yield is ≥85%.
[0011] The method for preparing the diatomic pair catalyst for hydrogenation of nitrile compounds comprises the following steps:
[0012] Step 1. Using nanodiamond as raw material, preparing nanodiamond / graphene composite material;
[0013] Step 2. loading rhodium atoms and cobalt atoms on the nanodiamond / graphene composite material in sequence by deposition precipitation and electrostatic adsorption respectively, to obtain a rhodium-cobalt nanodiamond / graphene composite material precursor;
[0014] Step 3. Place the rhodium-cobalt nanodiamond / graphene composite material precursor in a quartz tube, activate it under a hydrogen atmosphere, and obtain a diatomic pair catalyst for hydrogenation of nitrile compounds after cooling to room temperature.
[0015] In step 1, the preparation process of the nano-diamond / graphene composite material is as follows: the nano-diamond raw material is placed in an argon atmosphere at 1100° C. and 100 mL / min for calcination for 4 hours, and the nano-diamond / graphene composite material is obtained after the calcination.
[0016] In step 2, the process of the deposition precipitation method is as follows: 200 mg of the prepared nano-diamond / graphene composite material is mixed with 30 mL-40 mL of deionized water in a flask, the nano-diamond / graphene composite material is formulated into a suspension, and the suspension is placed in an 80°C-100°C oil bath and stirred evenly, and under heat preservation and stirring conditions, sodium carbonate solution or sodium formate solution is added dropwise to the suspension to adjust the pH value to 11-12, and then 4 mL of rhodium nitrate solution with a rhodium concentration of 0.075 g / L-0.5 g / L is added, and the mixture is kept warm and stirred for 1 hour before cooling to room temperature, and a rhodium-based nano-diamond / graphene composite catalyst precursor is obtained by suction filtration and vacuum drying;
[0017] The process of the electrostatic adsorption method is as follows: 4 mL of 5 mol / L-10 mol / L ammonia water is added to a beaker, 1 mL of a cobalt nitrate solution with a cobalt concentration of 0.5 g / L-1.5 g / L is added thereto, a rhodium-based nanodiamond / graphene composite material catalyst precursor is added thereto, ultrasonically dispersed for 2 min-10 min, stirred with a magnetic stirrer for 12 h-24 h under closed conditions, and a rhodium-cobalt nanodiamond / graphene composite material precursor is obtained after suction filtration, washing and drying.
[0018] During the pure hydrogen activation treatment in step 3, the activation treatment temperature is 200°C-300°C, and the activation treatment time is 1h-2h.
[0019] The diatomic pair catalyst for hydrogenation of nitrile compounds is used in the hydrogenation reaction of nitrile compounds. The catalyst is used in the hydrogenation reaction of nitrile compounds to generate secondary amine compounds, wherein the reaction temperature is 40°C to 60°C and the reaction pressure is 0.2MPa to 0.6MPa.
[0020] The unique method of sequential deposition precipitation and electrostatic adsorption adopted by the present invention overcomes the difficulty in forming rhodium-cobalt atomic pairs in the prior art. Traditional catalyst synthesis methods, such as impregnation methods, are often difficult to achieve uniform dispersion at the atomic level due to the uneven adsorption of metal ions on the carrier surface and the greater tendency of metal agglomeration. The present invention first forms an atomic-level dispersion layer of rhodium through a deposition precipitation method, and then uses an electrostatic adsorption method to utilize the mutual attraction between charges to accurately control the cobalt load, which not only optimizes the distribution of metal ions, but also ensures the stable formation of rhodium-cobalt diatomic pairs by regulating reaction conditions (such as pH value and temperature), thereby significantly improving the activity and selectivity of the catalyst.
[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0022] 1. The present invention is the first to prepare a rhodium-cobalt atomic pair catalyst on a diamond / graphene composite material, and is also the first to use a diatomic pair catalyst for the hydrogenation reaction of nitrile compounds.
[0023] 2. The present invention regulates the catalyst performance through the synergistic effect of rhodium and cobalt, effectively improving the catalyst activity and reducing the catalyst cost.
[0024] 3. The atomically dispersed rhodium-cobalt nanodiamond / graphene composite catalyst prepared by the present invention is applied to the hydrogenation reaction of nitrile compounds, achieving high conversion rate and high selectivity synthesis of secondary amines under mild conditions. The catalytic performance is greatly improved compared with the prior art, and it has low energy consumption, high safety and good economic benefits.
[0025] 4. The catalyst used in the present invention has low raw material cost, simple preparation, environmental protection and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 HAADF-STEM images of Rh1Co1 / ND@G; among them: (a) HAADF-STEM image at low magnification; (b) HAADF-STEM image at high magnification.
[0027] Figure 2 HAADF-STEM image of Rh1 / ND@G.
[0028] Figure 3 HAADF-STEM image of Co1 / ND@G.
[0029] Figure 4 It is a comparison chart of the apparent activation energy test results of Example 1 and Comparative Example 1.
[0030] Figure 5 It is a TOF comparison chart of Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0031] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] In the following examples and comparative examples, specific catalysts are represented by element symbols and English abbreviations, where Rh refers to rhodium, Co refers to cobalt, and ND@G refers to nanodiamond calcined at high temperature.
[0033] Example 1
[0034] In this embodiment, the preparation process of the catalyst is as follows:
[0035] The nano-diamond raw material was placed in an argon atmosphere at 1100°C and 100mL / min for calcination treatment for 4h. After calcination treatment, a nano-diamond / graphene composite material with a core-shell structure was obtained. 200mg of the nano-diamond / graphene composite material was weighed and placed in a 100mL round-bottom flask, 30mL of deionized water was added, and ultrasonic dispersion was uniform to obtain a suspension. The suspension was stirred evenly in an oil bath at 100°C, and then the pH value was adjusted to 11 with a sodium carbonate solution to obtain a nano-diamond / graphene composite dispersion. After calculating the amount of rhodium nitrate solution according to the load of 0.15wt% of the carrier mass, 4mL of 0.075g / L rhodium nitrate solution was measured and added to the dispersion. In an oil bath, the mixture was stirred at 100°C for 1h, then cooled to room temperature, and a rhodium-based nano-diamond / graphene composite catalyst precursor was obtained by suction filtration and vacuum drying. Add 4mL of 5mol / L ammonia water to a 10mL beaker, calculate the amount of cobalt nitrate solution according to the load of 0.25wt% of the carrier mass, measure 1mL of 0.5g / L cobalt nitrate solution and add it to the ammonia water, add the rhodium-based nanodiamond / graphene composite catalyst precursor thereto, disperse it evenly under ultrasound for 2min, and stir it with a magnetic stirrer for 24h under closed conditions. After suction filtration, washing and drying, the rhodium-cobalt nanodiamond / graphene composite precursor is obtained. After reduction at 300°C for 1h under a pure H2 atmosphere, an atomically dispersed rhodium-cobalt nanodiamond / graphene composite catalyst is obtained. The catalyst prepared in this embodiment is observed using a spherical aberration corrected high-angle annular dark field-scanning transmission electron microscope (HAADF-STEM). Both Rh and Co are atomically dispersed and distributed in pairs on the surface of the nanodiamond / graphene composite material ( Figure 1 ). The catalyst prepared in this example was used to test the hydrogenation performance of benzonitrile:
[0036] Catalyst performance test was performed using a tank reactor. 30 mg of Rh1Co1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was charged, the temperature was raised to 60°C, and the reaction was stirred for 3 hours. The yield of dibenzylamine was >98%.
[0037] The above catalyst was tested for apparent activation energy of benzonitrile hydrogenation:
[0038] Catalyst performance test was carried out using a tank reactor. 30 mg of Rh1Co1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was charged, and the temperature was raised to 40°C, 50°C, 60°C, and 70°C respectively, and the reaction was stirred for 15 minutes. The TOF at each temperature (T) was calculated using the formula (TOF = (amount of substance converted to benzonitrile per hour) / (amount of substance at metal active sites × metal dispersion)), and an XY image of 1000 / T-ln(TOF) was plotted. The test results are shown in Figure 2. Figure 4 shown.
[0039] The catalyst prepared in this example was subjected to TOF measurement of benzonitrile hydrogenation:
[0040] Catalyst performance test was performed using a tank reactor. 30 mg of Rh1Co1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was charged, and the temperature was raised to 60 °C and stirred for 15 min. The TOF was calculated using the formula (TOF = (amount of substance converted to benzonitrile per hour) / (amount of substance at metal active sites × metal dispersion)). The test results are shown in the figure. Figure 5 shown.
[0041] The catalyst prepared in this example was subjected to a benzonitrile hydrogenation cycle stability test:
[0042] The catalyst cycle stability test was carried out using a tank reactor. Weigh 30 mg of Rh1Co1 / ND@G catalyst and disperse it in 10 mL of methanol. Add 0.5 mmol of benzonitrile. Fill with 0.6 MPa H2, heat to 60 °C, and stir to react for 3 hours. Wash and dry the reacted catalyst and repeat the above steps. After 12 cycles, the yield of dibenzylamine is still >90%.
[0043] The catalyst prepared in this example was used to expand the substrate for hydrogenation of nitrile compounds:
[0044] Catalyst cycle stability test was carried out using a tank reactor. 30 mg of Rh1Co1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol. The substrates were p-methoxybenzonitrile, 3,5-dimethylbenzonitrile, 3,5-dimethoxybenzonitrile, p-chlorobenzonitrile, and acetonitrile, and the substrate concentration was 0.5 mmol. 0.6 MPa H2 was charged and the temperature was raised to 60 °C. Table 1 shows the catalyst activity evaluation results after the expansion of the nitrile compound hydrogenation substrate.
[0045] Table 1 Evaluation results of catalyst activity after expansion of nitrile hydrogenation substrates
[0046]
[0047] Example 2
[0048] In this embodiment, the preparation process of the catalyst is as follows:
[0049] The nano-diamond raw material was placed in an argon atmosphere at 1100°C and 100mL / min for calcination treatment for 4h. After calcination treatment, a nano-diamond / graphene composite material with a core-shell structure was obtained. 200mg of the nano-diamond / graphene composite material was weighed and placed in a 100mL round-bottom flask, 40mL of deionized water was added, and ultrasonic dispersion was uniform to obtain a suspension. The suspension was stirred evenly in an oil bath at 100°C, and then the pH value was adjusted to 12 with a sodium formate solution to obtain a nano-carbon carrier dispersion. 4mL of 0.5g / L rhodium nitrate solution was measured and added to the dispersion after calculating the amount of rhodium nitrate solution according to the load of 1wt% of the carrier mass. The mixture was stirred at 80°C in an oil bath for 1h, then cooled to room temperature, and a rhodium-based nano-diamond / graphene composite catalyst precursor was obtained by suction filtration and vacuum drying. Add 4mL of 10M ammonia water to a 10mL beaker, calculate the amount of cobalt nitrate solution according to the load of 0.75wt% of the carrier mass, measure 1mL of 1.5g / L cobalt nitrate solution and add it to the ammonia water, add the rhodium-based nanodiamond / graphene composite catalyst precursor, disperse it evenly by ultrasonication for 10min, and stir it with a magnetic stirrer for 12h under closed conditions. After filtration, washing and drying, the rhodium-cobalt nanodiamond / graphene composite precursor is obtained. After reduction at 200℃ for 2h in a pure H2 atmosphere, an atomically dispersed rhodium-cobalt nanodiamond / graphene composite catalyst is obtained.
[0050] Catalyst performance test was performed using a tank reactor. 5 mg of Rh1Co1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.2 MPa of H2 was charged, the temperature was raised to 40°C, and the reaction was stirred for 5 hours. The yield of dibenzylamine was >98%.
[0051] Example 3
[0052] In this embodiment, the preparation process of the catalyst is as follows:
[0053] The nano-diamond raw material is placed in an argon atmosphere at 1100°C and 100mL / min for calcination treatment, and the treatment time is 4h. After the calcination treatment, a nano-diamond / graphene composite material with a core-shell structure is obtained. 200mg of the nano-diamond / graphene composite material is weighed and placed in a 100mL round-bottom flask, 30mL of deionized water is added, and ultrasonic dispersion is uniform to obtain a suspension. The suspension is stirred evenly in an oil bath at 100°C, and then the pH value is adjusted to 11 with a sodium carbonate solution to obtain a nano-carbon carrier dispersion. After calculating the amount of rhodium nitrate solution according to the load of 0.15wt% of the carrier mass, 4mL of 0.075g / L rhodium nitrate solution is measured and added to the dispersion. Finally, the mixture is stirred at 100°C in an oil bath for 1h, then cooled to room temperature, and a rhodium-based nano-diamond / graphene composite catalyst precursor is obtained by suction filtration and vacuum drying. Add 4mL of 5M ammonia water to a 10mL beaker, calculate the amount of cobalt nitrate solution according to the loading amount of 0.5wt% of the carrier mass, measure 1mL of 1.0g / L cobalt nitrate solution and add it to the ammonia water, add the rhodium-based nanodiamond / graphene composite catalyst precursor, disperse it evenly under ultrasonication for 2min, and stir it with a magnetic stirrer for 24h under closed conditions. After filtration, washing and drying, the rhodium-cobalt nanodiamond / graphene composite precursor is obtained. After reduction at 300℃ for 1h in a pure H2 atmosphere, an atomically dispersed rhodium-cobalt nanodiamond / graphene composite catalyst is obtained.
[0054] Catalyst performance test was performed using a tank reactor. 30 mg of Rh1Co1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was charged, the temperature was raised to 60°C, and the reaction was stirred for 3 hours. The yield of dibenzylamine was >98%.
[0055] Example 4
[0056] In this embodiment, the preparation process of the catalyst is as follows:
[0057] The nano-diamond raw material was placed in an argon atmosphere at 1100°C and 100mL / min for calcination treatment for 4h. After calcination treatment, a nano-diamond / graphene composite material with a core-shell structure was obtained. 200mg of the nano-diamond / graphene composite material was weighed and placed in a 100mL round-bottom flask, 30mL of deionized water was added, and ultrasonic dispersion was uniform to obtain a suspension. The suspension was stirred evenly in an oil bath at 100°C, and then the pH value was adjusted to 11 with a sodium carbonate solution to obtain a nano-carbon carrier dispersion. 4mL of 0.075g / L rhodium nitrate solution was measured and added to the dispersion after calculating the amount of rhodium nitrate solution according to the load of 0.5wt% of the carrier mass. The mixture was stirred at 100°C in an oil bath for 1h, then cooled to room temperature, and a rhodium-based nano-diamond / graphene composite catalyst precursor was obtained by suction filtration and vacuum drying. Add 4mL of 5mol / L ammonia water to a 10mL beaker, calculate the amount of cobalt nitrate solution according to the loading amount of 0.5wt% of the carrier mass, measure 1mL of 0.5g / L cobalt nitrate solution and add it to the ammonia water, add the rhodium-based nanodiamond / graphene composite catalyst precursor, disperse it evenly under ultrasonication for 2min, and stir it with a magnetic stirrer under closed conditions for 24h. After filtration, washing and drying, the rhodium-cobalt nanodiamond / graphene composite precursor is obtained. After reduction at 300℃ for 1h in a pure H2 atmosphere, an atomically dispersed rhodium-cobalt nanodiamond / graphene composite catalyst is obtained.
[0058] Catalyst performance test was performed using a tank reactor. 10 mg of Rh1Co1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was charged, the temperature was raised to 60°C, and the reaction was stirred for 3 hours. The yield of dibenzylamine was >98%.
[0059] Comparative Example 1:
[0060] The method for preparing the catalyst in this method is the same as that in Example 1, except that: no cobalt is loaded during the catalyst preparation process, and the rhodium atom loading amount is 0.15wt% of the carrier mass, denoted as Rh1 / ND@G. Using HAADF-STEM to observe Comparative Example 1, Rh is distributed in the form of single atoms on the surface of the nanodiamond / graphene composite material ( Figure 2 ). The catalyst performance was tested using a tank reactor. 30 mg of Rh1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was charged, the temperature was raised to 60°C, and the reaction was stirred for 3 hours. The yield of dibenzylamine was 85%.
[0061] The above catalyst was tested for apparent activation energy of benzonitrile hydrogenation:
[0062] Catalyst performance test was carried out using a tank reactor. 30 mg of Rh1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was charged, and the temperature was raised to 40°C, 50°C, 60°C, and 70°C respectively, and the reaction was stirred for 15 minutes. The TOF at each temperature (T) was calculated using the formula (TOF = (amount of substance converted to benzonitrile per hour) / (amount of substance at metal active sites × metal dispersion)), and an XY image of 1000 / T-ln(TOF) was plotted. The test results are shown in Figure 2. Figure 4 shown.
[0063] The TOF measurement of benzonitrile hydrogenation was carried out using the catalyst prepared in Comparative Example 1:
[0064] Catalyst performance test was performed using a tank reactor. 30 mg of Rh1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was charged, and the temperature was raised to 60 °C and stirred for 15 min. The TOF was calculated using the formula (TOF = (amount of substance converted to benzonitrile per hour) / (amount of substance at metal active sites × metal dispersion)). The test results are shown in the figure. Figure 5 shown.
[0065] Comparative Example 2:
[0066] The difference between this example and Example 1 is that rhodium is not loaded during the catalyst preparation process, and the cobalt atom loading is 0.25wt% of the carrier mass, denoted as Co1 / ND@G. Using HAADF-STEM to observe Comparative Example 2, Co is distributed in the form of single atoms on the surface of the nanodiamond / graphene composite material ( Figure 3 ). The catalyst performance was tested using a tank reactor. 30 mg of Co1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was introduced, the temperature was raised to 60 °C, and the reaction was stirred for 3 h. There was almost no yield of dibenzylamine.
[0067] The above catalyst was subjected to TOF determination of benzonitrile hydrogenation:
[0068] Catalyst performance test was performed using a tank reactor. 30 mg of Co1 / ND@G catalyst was weighed and dispersed in 10 mL of methanol, and 0.5 mmol of benzonitrile was added. 0.6 MPa of H2 was charged, and the temperature was raised to 60 °C and stirred for 15 min. The TOF was calculated using the formula (TOF = (amount of substance converted to benzonitrile per hour) / (amount of substance at metal active sites × metal dispersion)). The test results are shown in the figure. Figure 5 shown.
[0069] Based on the above results of catalytic hydrogenation of nitrile compounds, the yield of catalytic hydrogenation of nitrile compounds in Example 1 is the highest, and the yields of other nitrile compound catalysts are relatively high; it shows that the atomic-level dispersed rhodium cobalt nanodiamond / graphene composite catalyst of the present invention has high hydrogenation catalytic activity for catalytic hydrogenation of nitrile compounds, high selectivity for secondary amines, and good cycle stability. Moreover, the catalyst synthesis method is mature, easy to recycle and environmentally friendly.
[0070] The above examples are for reference only. Technical solutions that are similar to the present invention or extended from the concept of this patent are all within the protection scope of the present invention.
Claims
1. A diatomic pair catalyst for hydrogenation of nitrile compounds, characterized in that: The catalyst uses a nano-diamond / graphene composite material as a carrier and rhodium-cobalt diatoms as active materials; rhodium and cobalt are uniformly loaded on the surface of the nano-diamond / graphene composite material carrier in the form of diatomic pairs, and form bonds with carbon atoms on graphene defects; In the process of hydrogenation of nitrile compounds to generate secondary amine compounds, when the reaction time is 6h to 8h, the product yield is ≥85%.
2. The diatomic pair catalyst for hydrogenation of nitrile compounds according to claim 1, characterized in that: The nano-diamond / graphene composite material is a core-shell structure formed by taking nano-diamond as a core and graphene rich in defects as a shell.
3. The diatomic pair catalyst for hydrogenation of nitrile compounds according to claim 1, characterized in that: In the catalyst, the content of rhodium is 0.15wt%-1.0wt% of the carrier mass, and the content of cobalt is 0.25wt%-0.75wt% of the carrier mass.
4. The method for preparing a diatomic pair catalyst for hydrogenation of nitrile compounds according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1. Using nanodiamond as raw material, preparing nanodiamond / graphene composite material; Step 2. loading rhodium atoms and cobalt atoms on the nanodiamond / graphene composite material in sequence by deposition precipitation and electrostatic adsorption respectively, to obtain a rhodium-cobalt nanodiamond / graphene composite material precursor; Step 3. Place the rhodium-cobalt nanodiamond / graphene composite material precursor in a quartz tube, activate it under a hydrogen atmosphere, and obtain an atomically dispersed rhodium-cobalt nanodiamond / graphene composite material catalyst after cooling to room temperature.
5. The method for preparing a diatomic pair catalyst for hydrogenation of nitrile compounds according to claim 4, characterized in that: In step 1, the preparation process of the nano-diamond / graphene composite material is as follows: the nano-diamond raw material is placed in an argon atmosphere at 1100° C. and 100 mL / min for calcination for 4 hours, and the nano-diamond / graphene composite material is obtained after the calcination.
6. The method for preparing a diatomic pair catalyst for hydrogenation of nitrile compounds according to claim 4, characterized in that: In step 2, the process of the deposition precipitation method is as follows: 200 mg of the prepared nano-diamond / graphene composite material is mixed with 30 mL-40 mL of deionized water in a flask, the nano-diamond / graphene composite material is prepared into a suspension, and the suspension is placed in an 80°C-100°C oil bath and stirred evenly. Under the condition of heat preservation and stirring, sodium carbonate solution or sodium formate solution is added dropwise to the suspension to adjust the pH value to 11-12, and then 4 mL of rhodium nitrate solution with a rhodium concentration of 0.075 g / L-0.5 g / L is added, and the mixture is kept warm and stirred for reflux for 1 hour, then cooled to room temperature, and filtered and vacuum dried to obtain a rhodium-based nano-diamond / graphene composite catalyst precursor.
7. The method for preparing a diatomic pair catalyst for hydrogenation of nitrile compounds according to claim 4, characterized in that: In step 2, the process of the electrostatic adsorption method is as follows: 4 mL of 5 mol / L-10 mol / L ammonia water is added to a beaker, 1 mL of a cobalt nitrate solution having a cobalt concentration of 0.5 g / L-1.5 g / L is added thereto, a rhodium-based nano-diamond / graphene composite material catalyst precursor is added thereto, ultrasonically dispersed for 2 min-10 min, stirred with a magnetic stirrer under closed conditions for 12 h-24 h, and a rhodium-cobalt nano-diamond / graphene composite material precursor is obtained after suction filtration, washing and drying.
8. The method for preparing a diatomic pair catalyst for hydrogenation of nitrile compounds according to claim 4, characterized in that: In step 3, during the pure hydrogen activation treatment, the activation treatment temperature is 200°C-300°C, and the activation treatment time is 1h-2h.
9. Use of the diatomic pair catalyst for hydrogenation of nitrile compounds according to any one of claims 1 to 3, characterized in that: The catalyst is used for hydrogenation reaction of nitrile compounds to generate secondary amine compounds.
10. The use of the diatomic pair catalyst for hydrogenation of nitrile compounds according to claim 9, characterized in that: The reaction temperature is 40°C to 60°C, and the reaction pressure is 0.2MPa to 0.6MPa.